2023
DOI: 10.3390/brainsci13040655
|View full text |Cite
|
Sign up to set email alerts
|

What Do Differences between Alternating and Sequential Diadochokinetic Tasks Tell Us about the Development of Oromotor Skills? An Insight from Childhood to Adulthood

Abstract: Oral diadochokinetic (DDK) tasks are common research and clinical tools used to test oromotor skills across different age groups. They include alternating motion rate (AMR) and sequential motion rate (SMR) tasks. AMR tasks involve repeating a single syllable, whereas SMR tasks involve repeating varying syllables. DDK performance is mostly discussed regarding the increasing rates of AMR and SMR tasks from childhood to adulthood, although less attention is given to the performance differences between SMR and AMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In our study, we also observed a slower rate for /pataka/ before and after surgery. Some studies suggest that adults achieve higher rates of /pataka/ compared to same-syllable repetitions [24]. In that respect, when compared to the same syllable repetitions and against the reference value, the slower rate observed in this study might represent a subclinical disturbance of motor speech.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…In our study, we also observed a slower rate for /pataka/ before and after surgery. Some studies suggest that adults achieve higher rates of /pataka/ compared to same-syllable repetitions [24]. In that respect, when compared to the same syllable repetitions and against the reference value, the slower rate observed in this study might represent a subclinical disturbance of motor speech.…”
Section: Discussionmentioning
confidence: 43%
“…Although widely used in motor speech assessments, DDK is still a subject of debate. Some studies propose that there is insufficient empirical evidence that would support the clinical use of nonspeech parameters in analyzing motor speech in patients with neurological disorders [23], while others suggest that DDK performance mirrors speech proficiency [24].…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, the DDK test is used to detect types of motor speech disorders: (i) abnormalities of articulation secondary to weakness or incoordination of the muscles required for speech (dysarthria), and (ii) speech production difficulties due to sequencing or programming of muscles in the absence of weakness or incoordination (apraxia) [ 24 ]. Two types of DDK tasks are commonly used: Alternating Motion Rate refers to the rapid repetition of single syllables such as ‘pa’ or ‘ta’ or ‘ka’; Sequential Motion Rate refers to the rapid repetition of syllables in sequence, ‘pa-ta-ka.’ Both tasks are valid and sensitive motor tests and used in the differential diagnosis of adults with a variety of neurological disorders [ 25 , 26 ]. Alternating Motion Rates are less affected by linguistic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Utterance onset times occur later for words containing similar sounds than for words containing dissimilar sounds in production experiments ( 15 ). Additionally, while repeated syllables are easier for children to produce and learn ( 16 ), adults exhibit a faster speech rate for sequences of different syllables ( 17 ), striking given that identical consonants are common in nursery words (e.g., mama, cookie, etc.).…”
mentioning
confidence: 99%